The MicroRNA Family Gets Wider: The IsomiRs Classification and Role - Tomasello, Luisa; Distefano, Rosario; Nigita, Giovanni; Croce, Carlo M. (Frontiers in Cell and Developmental Biology, 2021)
MicroRNAs (miRNAs or miRs) are the most characterized class of non-coding RNAs and are engaged in many cellular processes, including cell differentiation, development, and homeostasis. MicroRNA dysregulation was observed in several diseases, cancer included. Epitranscriptomic is a branch of epigenomics that includes all RNA modifications occurring after DNA transcription and RNA synthesis and involving coding and non-coding RNAs. The development of new high throughput technologies, especially deep RNA sequencing, has facilitated the discovery of miRNA isoforms (named isomiRs) resulting from RNA modifications mediated by enzymes, such as deaminases and exonucleases, and differing from the canonical ones in length, sequence, or both. In this review, we summarize the distinct classes of isomiRs, their regulation and biogenesis, and the active role of these newly discovered molecules in cancer.